Effect of Catheterization Time combined with Volume on Patients with Incomplete Bladder Emptying after Stroke - Huiying ZHANG; Xiuqin SHAO; Tianzi ZOU; Xiaoyue LI; Shuang QUAN; Tongzhou MI (康复学报, 2020)
Objective:To observe the effect of catheterization time combined with catheterization volume on patients with incomplete bladder emptying (IBE) after stroke.Methods:A total of 62 patients with IBE after stroke were divided into the control group (n=30) and the observation group (n=32) respectively, in the first affiliated hospital of Nanchang University from June to December 2017, according to the random number table method. The control group was given routine rehabilitation treatment such as transcutaneous nerve stimulation, acupuncture, bladder function retraining, and at the same time, the patients were given time-type intermittent catheterization once every 4-8 hours. The observation group was given catheterization time combined with catheterization volume on the basis of routine rehabilitation treatment in the control group. The patients were classified according to the results of urodynamics and bladder volume pressure measurement. Bladder volume before urination and residual urine volume after micturition were dynamically monitored by BladderScar (BVI9400) and micturition diary bedside, and intermittent catheterization was performed when the urine volume reached"bladder safety capacity". Before and after intervention, the patients'micturition volume, times of micturition and interval time of micturition were observed; the bladder safety capacity and residual urine volume were assessed by Bladder capacity tester; the incidence of urinary tract infection was assessed by laboratory urine culture; the reimplantation of indwelling catheter was observed in the two groups.Results:Before intervention, there was no significant difference in micturition volume, micturition times, voiding time interval, bladder volume, residual urine volume, urinary tract infection and repeated indwelling catheter times between the two groups (P>0.05). Compared with those before intervention, the urine volume and bladder volume in the observation group increased significantly and the residual urine volume decreased significantly after intervention for three weeks, and the difference was statistically significant (P<0.05). Compared with the control group, the micturition volume and bladder capacity of the observation group were significantly higher, and the micturition times and residual urine volume were significantly lower after intervention for three weeks in the observation group, and the difference was statistically significant (P<0.05). There was no significant difference in urinary tract infection rate and repeated indwelling catheter rate between the two groups after intervention (P>0.05).Conclusion:Catheterization time combined with volume intermittent catheterization is helpful for patients to re-establish micturition reflex arc, increase self-micturition volume and bladder capacity, reduce residual urine volume and average daily micturition times according to accurate bladder safety capacity. It is worthy of clinical application to promote the recovery of patients'autonomous voiding function and reduce the risk of urinary tract infection.